Pathological online game use of secondary vocational school students: Current situation and its relation to self-esteem and self-identity - Yang, Lixian; Chen, Yuan; Zhang, Mengxia; Zhang, Jinkun (Frontiers in Psychiatry, 2022)
Secondary Vocational School Students are particularly susceptible to online game addiction due to adolescent characteristics and superimposed pressures of academic and employment. Based on the theoretical framework of self-identity and self-esteem, the present research conducted a questionnaire survey using samples of secondary vocational school students to investigate the relationship between pathological online game use (POGU), self-esteem and self-identity. The results showed that 15.56% of secondary vocational students’ level of POGU met the diagnostic criteria, and POGU and self-esteem appeared significant differences in gender and family types. Moreover, lower self-esteem and self-identity were associated with higher POGU and self-esteem played a partial mediating role in the relationship between self-identity and POGU. We briefly discussed practical implications of our findings and the future research.